“It Can’t Be Like Last Time” – Choices Made in Early Pregnancy by Women Who Have Previously Experienced a Traumatic Birth - Greenfield, Mari; Jomeen, Julie; Glover, Lesley (Frontiers in Psychology, 2019)
Background A significant number of women experience childbirth as traumatic. These experiences are often characterised by a loss of control coupled with a perceived lack of support and inadequate communication with health care professionals. Little is known about the choices women make in subsequent pregnancy(s) and birth(s), or why they make these choices. This study aimed to understand these choices and explore the reasons behind them. Methods A longitudinal Grounded Theory Methods (GTM) study involving 9 women was conducted. Over half of the participants had a formal diagnosis of PTSD and/or PND related to the previous birth. Interviews were carried out at 3 timepoints perinatally. These findings are from the first interviews at 12-20 weeks. Results From the first days of pregnancy, this cohort of women were focused on concerns that this birth would be a repeated traumatic experience. The women were deliberately searching out and analysing information about their choices in this pregnancy and birth, and making plans which had two aims; firstly to avoid a repeat of their previous birth experience, and secondly to avoid a loss of control to other people during the birth. The women considered a range of birth choices, from elective caesareans to freebirth. Some women felt well supported by those around them, including health care professionals, partners, friends and family. Others did not, and were anticipating conflict in trying to assert their birth choices. Many early relationships with health care professionals were characterised by fear and mistrust. Discussion Women who have previously experienced a traumatic birth become pregnant again, have a strong desire to avoid a repeat experience and to feel in control of their birth choices. Access to robust information appears to help reduce uncertainty and arm women in their discussions with professionals. Similarly making plans and seeking to have them agreed with health care professionals at an early stage is used a way to reduce the risk of having a further traumatic experience. Implications for practice include supporting women in formulating and confirming pregnancy and birth plans at an early stage to reduce uncertainty and foster a sense of control